The Painted Musicians in Longthorpe Tower. Issue 1 (1st January 2014) - Buckle, Alexandra
Abstract: This article examines the instrumentalists painted on the vault of the first-floor room of the surviving tower of Longthorpe Manor, near Peterborough, built by Robert of Thorpe in about 1330. Longthorpe Tower is currently being reinterpreted by English Heritage, and, as a result, new photos of the wall paintings have been taken, which allow greater clarity of content. This article will focus on the seven instrumentalists, once eight, which now survive in each quadrant of the vault. It will show that, although the paintings are in a poor state of preservation, there is much to be gleaned from the extant instrumentalists. Previous scholarship has focused on the nativity scene, apostles, and royal symbols, painted on the walls below the vault. Here the role of the musicians and instruments in this iconographical scheme is examined for the first time. In addition, the importance of these instruments to musicians and musicologists is assessed. Detailed diagrams of the instruments are given, along with a commentary on the extent to which these painted representations can be read as legitimate instruments capable of a realistic performance practice. The role of music within the iconographical scheme of Robert of Thorpe's tower will also be provided, showing how it adds to the portrayal of Thorpe as a religious and learned man of high station. Musicians and the role of music are often neglected in the interpretations of historic schemes. This article calls for a consideration of music alongside wider iconographic schemes and clearly shows the extent to which music can help unravel complex messages.